2008
DOI: 10.2175/193864708788808069
|View full text |Cite
|
Sign up to set email alerts
|

Odor Emissions from Anaerobically Digested Biosolids During Onsite Storage and Land Application: Impacts of Lime Dosing and the Type of Dewatering Process Used (Belt Presses Versus Centrifuges)

Abstract: Odor emissions data were collected during a Biosolids Fecal Coliform Regrowth Study in order to gain insight into odor emissions from anaerobically digested biosolids stored on site and during land application. Sampling and concentration analyses were completed for the following: odor (in terms of dilutions to threshold), ammonia, speciated sulfur compounds, volatile organic compounds, speciated amine compounds, and volatile organic acids. The effects of liming centrifuge dewatered biosolids were assessed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These differences could also be attributed to the different dewatering processes. It was previously suggested that higher shear forces (as in centrifugation) release more labile proteins, which then serve as the source for generation of reduced sulfur VOCs (Subramanian et al, 2005; Feltner et al, 2008). However, a comparison between the two dewatering methods cannot be made based on present data because the two dewatering methods were not compared for one sludge source.…”
Section: Resultsmentioning
confidence: 99%
“…These differences could also be attributed to the different dewatering processes. It was previously suggested that higher shear forces (as in centrifugation) release more labile proteins, which then serve as the source for generation of reduced sulfur VOCs (Subramanian et al, 2005; Feltner et al, 2008). However, a comparison between the two dewatering methods cannot be made based on present data because the two dewatering methods were not compared for one sludge source.…”
Section: Resultsmentioning
confidence: 99%